SyncML Synchronizing and Managing Your Mobile Data - Hansmann, Uwe; Mettala, Riku M.; Purakayastha, Apratim; Thompson, Peter (Prentice Hall PTR, 2002)
Annotation
Keywords: Synchronous data transmission systems; Wireless communication systems -- Standards; Mobile communication systems -- Standards; Computer network protocols; Transmission synchrone; Transmission sans fil; Normes; Radiocommunications mobiles; Normes; Protocoles de réseaux d'ordinateurs; Mobile communication systems; Standards; Wireless communication systems; Standards